PELATIHAN PENGOLAHAN KRIPIK PISANG BUMBU INSTAN ”SUNA CEKUH” DI DESA TIGA BANGLI - I G.A. Lani Triani; A.A.M.D. Anggreni; M. Indri H.A; A.S. Duniaji (Buletin Udayana Mengabdi, 2014)
Banana is one of the fruits that is always used for religious ceremony in Bali. Banana is rich in hydrocarbon, vitamin and mineral. Usually after harvesting, banana easily becomes spoiled and causes it banana having low quality. Furthermore, good agricultural manufacturing was rquired to improve the quality of the fruit. The community service was conducted on April- August 2014 to the woman farmer Group of Bunga Sahabat at the village of Tiga of Susut district, Bangli Regency. The women farmer group was given the knowledge and skill in order to improve the processing of banana as Banana Chips with “Suna Cekuh” spices. “Suna Cekuh” spices is the combination of garlic, zedoary and salt that was homogenized.to make instant powder.The women farmer group has proven their skill and ability to produce the good quality product. of banana chips with “Suna Cekuh” spices. The banana chip with “Suna Cekuh” spices was accepted by the highly preferred panelist.Keywords : chip, suna-cekuh, hydrocarbon